Health related news in the printed media [Yazili basinda çikan saǧlik haberlerİnİn İncelenmesİ] - (:unkn) unknown (My University, 2010)
Objectives: Health news that appears in the press is of controvertial scientific quality. Moreover, many physicians believe that the press coverage of physicians, negatively affects their image. Methods: In this study press reports of health news reports for May and June of 2006 and 2008 were investigated. These news items were classified as health policy news, health information news, and news about physicians. News about physicians was further classified as positive or negative and health information news as with or without references. Results: In May and June of 2006 a total 3155 health-related news items were found. 913 (28.9%) were about health policies, 1126 were health information news (35.6%) and 112 (3.5%) were about physicians. Of the health information news 81.4% of the items had references while 18.6% did not. 83.9% of news items about doctors were regarded as positive, whereas 16.1% consisted of negative news. In 2008, 3543 health news items were found. 699 (19.7%) were related to health policies, 1824 (51.4%) were health information news and 122 (3.4%) were about physicians. 45.9% of the news items about physicians were positive whereas 54.1% were negative. Conclusion: The number of health-related news items are increasing in the two years studied here and show a significant increase in negative news about the physicians while health policy news items are declining.
Keywords: Health news; Physicians; Printed press